Crosslinking Of Alkaline Peroxide Oil Palm Empty Fruit Bunch Fibres Via Azide-Alkyne Click Chemistry: Synthesis And Characterization - Ahmad, Noor Afiqah (2017)
There has been growing interest in fibre modification for several industrial applications. The modifications have mostly been done to improve the fibre properties. However, the information regarding fibre modification via click chemistry is still limited. In this work, oil palm empty fruit bunch was extracted via Alkaline Peroxide Pulping (APP). Then the extracted pulp was beaten to 8000 revolutions using PFI mill. The resulting fibres were chemically modified using two strategies of click chemistry were evaluated for modifying empty fruit bunch fibre without the addition of copper catalyst, which was dispersibility and crosslinking. In both of these modification strategies, there were two methods to modified the fibre.